Pengaruh Pengelolaan Alokasi Dana Desa Terhadap Pemberdayaan Dan Peningkatan Kesejahteraan Masyarakat Desa Maurisu Selatan Kecamatan Bikomi Selatan - Kamilaus Konstanse Oki; Margaretha Diana Pangastuti; Noviana Ua (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2020)
Abstract The Village Fund Allocation aims to finance village government apparatus allowances, infrastructure development, social activities and investment in the economic development of rural communities. South Maurisu Village in South Bikomi District is one of the villages receiving Village Fund Allocation. Village fund management is an important factor in empowering and improving the welfare of the people of South Maurisu Village. The purpose of this study was to determine the effect of village fund management on community empowerment and welfare. The study was conducted in South Maurisu Village with a sample of 87 people from village officials and the community. Verification analysis in this study uses statistical test equipment, namely the Variance-based structural equation test or better known as Partial Least Square (PLS). The results of the analysis show a positive relationship between village fund management on community empowerment and welfare.